2012
DOI: 10.1007/s00011-012-0458-2
|View full text |Cite
|
Sign up to set email alerts
|

Associations between interleukin-10 polymorphisms and susceptibility to psoriasis: a meta-analysis

Abstract: This meta-analysis shows that the IL-10-1082 G/A polymorphism confers susceptibility to psoriasis in Asians, and suggests that the IL-10 promoter -1082 polymorphism has an ethnicity-specific effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…There are several polymorphisms associated with risk of psoriasis, including signal transducer and activator of transcription 4 (STAT4), TaqI polymorphisms in vitamin D receptor (VDR) gene, interleukin-10 (IL-10) polymorphisms and LCE3B genes [35,36]. But no studies investigated the gene-gene interactions in the associations of TNF-α 308 G/A and 238 G/A polymorphisms with psoriasis risk.…”
Section: Discussionmentioning
confidence: 99%
“…There are several polymorphisms associated with risk of psoriasis, including signal transducer and activator of transcription 4 (STAT4), TaqI polymorphisms in vitamin D receptor (VDR) gene, interleukin-10 (IL-10) polymorphisms and LCE3B genes [35,36]. But no studies investigated the gene-gene interactions in the associations of TNF-α 308 G/A and 238 G/A polymorphisms with psoriasis risk.…”
Section: Discussionmentioning
confidence: 99%
“…25 A meta-analysis of eight studies involving 1018 psoriasis patients and 1186 controls shows that the IL-10-1082 G/A polymorphism confers susceptibility to psoriasis in Asians, and suggests that the IL-10 promoter -1082 polymorphism has an ethnicity-specific effect. 26 The molecular mechanism of the association between ACE I/D polymorphism and the risk of psoriasis is still relatively unclear. ACE and its related substrates or products are known to have wide-ranging effects on cutaneous immune and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…analysed three SNPs at the IL10 5ʹ flanking region [−1082 (rs1800896), −592 (rs1800872), −819C/T (rs1800871)] and identified that the IL10 ACC haplotype is associated with lower levels of disease activity and ATA haplotype with persistent eruption . The significant association of the IL10 ‐1082G allele with psoriasis ( P = 0·011) has been reported in a meta‐analysis involving Asian patients with psoriasis ( N = 1018) and controls ( N = 1186) …”
Section: Discussionmentioning
confidence: 86%
“…24 The significant association of the IL10-1082G allele with psoriasis (P = 0Á011) has been reported in a meta-analysis involving Asian patients with psoriasis (N = 1018) and controls (N = 1186). 53 Associations between IL19, IL20 and IL24 polymorphisms and psoriasis have also been assessed. Some studies found a significant association between psoriasis and IL19 SNP rs2243188, IL20 SNP rs2981572 and IL20 SNP rs1518108 in a cohort of unrelated white patients with psoriasis.…”
Section: Discussionmentioning
confidence: 99%